2018
DOI: 10.1051/matecconf/201820302011
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Legal Aspects and Contract Requirements of the BIM Practice in Malaysian Construction Industry

Abstract: Legal, contractual issues and the absence of appropriate protocols have been ranked as critical barriers associated with the implementation of Building Information Modelling (BIM). As to date, these issues are under studied and there is lack of framework addressing legal and contractual measures ensuring contract best practice in BIM project setting and legal environment in Malaysia. This research attempts to review legal issues and two common local standard forms of contract in order to highlight provisions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Finally, the legal and contractual issues pose serious challenges not specifically for the I4.0 adoption only but more generally, for the adoption of new technologies and innovative ways of work. Various studies have already shown that legal and contractual problems lead to poor adoption of new technologies and digitalization (Abubakar et al , 2014; Jo et al , 2018; Li et al , 2019). Even though this challenge was ranked as the least important among other challenges, the responding companies reported that they successfully handle this barrier for their I4.0 adoption.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the legal and contractual issues pose serious challenges not specifically for the I4.0 adoption only but more generally, for the adoption of new technologies and innovative ways of work. Various studies have already shown that legal and contractual problems lead to poor adoption of new technologies and digitalization (Abubakar et al , 2014; Jo et al , 2018; Li et al , 2019). Even though this challenge was ranked as the least important among other challenges, the responding companies reported that they successfully handle this barrier for their I4.0 adoption.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In another study, Abubakar et al (2014) implied that legal and contractual constraints lead to reluctance toward BIM adoption in the Nigerian construction industry. Jo et al (2018) further revealed that legal and contractual issues are among the critical barriers for BIM implementation in the Malaysian construction industry. Li et al (2019) stated that there are several aspects associated with untested legal issues and clear contract terms in the construction industry to reduce the likelihood of risks leading to Major challenges for industry 4.0 adoption unintended obligations and disputes.…”
Section: Data Protection and Cybersecuritymentioning
confidence: 99%
“…This issue leads to the blurring of intellectual property rights [208][209][210]. Given that the stakeholders are collaborating on the same platform and files, the boundaries between contributions from different stakeholders are challenging to define [209,[211][212][213][214][215]. Moreover, this obstacle can cause conflicts of interest and intellectual property ownership between stakeholders [208][209][210]214].…”
Section: The Barriers To Green Building Development In Chinamentioning
confidence: 99%
“…In executing tasks within the BIM environment, concerns on the issue of confidentiality, data ownership and data security became apparent due to the integration of multiple proprietary information in the process of developing building models (Fan, 2014;Ming Jo et al, 2018;Liou, Lee, & Chong;. In this collaborative and integrative working condition, the use of copyrighted materials is inevitable for all parties involved including the employers who would want to utilise such intellectual property for post-completion work such as renovation, maintenance, and facility extension.…”
Section: Legal Issuesmentioning
confidence: 99%
“…The adoption of BIM, which requires the sharing of data, could promote all parties to work collaboratively and allowing parties to jointly use the model for the tasks to be executed efficiently. This collaborative working condition in BIM brings up concerns on the legal issue of intellectual property infringement and ownership of data, which is absent in the previous transactional-type contract and paper-based design (Alwash et al, 2017;Ming Jo et al, 2018;Mohamad Izani, Zulhabri & Norfashiha, 2019).…”
Section: Intellectual Property Rights (Ipr) In Building Information Modelling (Bim) Construction Projectsmentioning
confidence: 99%